Recommendations derived from the accreditation of educational programs: Analysis of a public state university in Mexico - José Alfonso Jiménez Moreno; Salvador Ponce Ceballos (Arizona State University, 2020)
The article addresses the problem of accreditation of educational programs in Mexico. The importance of this type of evaluation is generated based on the policies in which higher education in Latin America is circumscribed. The objective of the research was to carry out a documentary analysis of 21 accreditation documents of seven programs of a public university over three periods, in order to classify the recommendations made by the accrediting instances; The resulting units or categories were as follows: Academic Staff, Students, Curriculum, Collaboration, Research and Program Management. The results show a lack of conceptual delimitation and compliance with international standards in the 21 documents, as well as information that suggests the university should increase the competitiveness of its programs, consolidate collegial work, strength trajectories, and meet the needs of the environment. The authors conclude that there is a need to make explicit the evaluation model that supports the accreditations. In addition, they  describe how the accreditation promotes academic productivity and the establishment of basic conditions for the organization and operation of educational programs.